2015
DOI: 10.14260/jemds/2015/1517
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study on Road Traffic Accident in Urban West - Bengal

Abstract: Road traffic injuries nowadays take the place as a major public health problem constituting leading cause of mortality and morbidity globally and in India, more than a million are injured annually and about a lakh are killed in road traffic accidents. Road traffic accidents are defined as a collision involving at least one vehicle in motion on a public or private road that results in at least one person being injured or killed. In this context, an epidemiological study was conducted in a teaching hospital of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…24 Unsafe pattern of driving is closely associated to gender and age of an individual. 19 In the present study, males of active age group 20 to 29 years were found to be responsible for overspeeding, and reckless and inexperienced driving in most of the cases. Moreover high-speed road crashes result in more severe injuries.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…24 Unsafe pattern of driving is closely associated to gender and age of an individual. 19 In the present study, males of active age group 20 to 29 years were found to be responsible for overspeeding, and reckless and inexperienced driving in most of the cases. Moreover high-speed road crashes result in more severe injuries.…”
Section: Discussionmentioning
confidence: 44%
“…However, previously maximum number of cases was reported on working days. 18 Regarding variation according to months of the year, highest number of the accidents was recorded in July and August by some 5,19 which are the months of monsoon season. The road becomes muddy and slippery causing more accidents.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] in Puducherry and Biswas S et al . [ 5 ] in West Bengal. Such a finding may be because in our society mostly male members of the family constitute the breadwinners of their families, and thus, are more involved in outdoor activities, and therefore, prone to accidents.…”
Section: Discussionmentioning
confidence: 99%